HOPE4MCI trial: First trial targeting reduction of hippocampal overactivity to treat mild cognitive impairment due to Alzheimer's disease with AGB101. (31st December 2021) - Rosenzweig‐Lipson, Sharon; Barton, Russell; Gallagher, Michela; Mohs, Richard
Abstract: Background: AD pathophysiological pathways involving both amyloid and tau have been functionally linked to excessive neural activity, with heightened neural activity causing dysfunction and progressive spread of pathology in the disease from an origin in the medial temporal lobe/hippocampus. Like hippocampal overactivity, recent evidence has demonstrated an association of amyloid and p‐tau 217 in early AD, with progressive elevation of p‐tau217 as the disease progresses. Substantial clinical evidence also indicates that hippocampal overactivity longitudinally predicts subsequent cognitive decline/conversion to dementia due to AD. AGB101 (low dose levetiracetam) demonstrates efficacy on a range of AD‐related molecular, synaptic, electrophysiological, functional and behavioral endpoints across models and species. Clinical proof of concept for this therapeutic hypothesis was demonstrated with AGB101 in a Phase 2A study that showed a reduction in hippocampal overactivity resulted in improvement in task related memory performance. To further examine this hypothesis, the HOPE4MCI trial is investigating the effects of AGB101 (low dose levetiracetam, 220 mg extended release) in a 78‐week protocol using tau biomarkers ([11C]MK 6420 pet imaging and p‐tau 217 plasma) alongside CDR‐SB (sole primary endpoint) for clinical/cognitive efficacy in MCI due to AD. Methods: This is a multicenter, randomized, double‐blind, placebo‐controlled, 78‐week, fixed‐dose study evaluating AGB101 versus placebo as a treatment for slowing the progression of MCI due to AD. Inclusion criteria: Subjects must meet the following inclusion criteria at screening: 1) Subjects between 55 and 85 years old 2) Have MCI due to AD consistent with the NIA‐AA criteria: MMSE (24‐30); CDR (0.5); Impaired delayed recall on the ISLT; essentially preserved ADLs 3) Evidence of an amyloid‐positive PET scan. Results: The HOPE4MCI trial has completed enrollment with 164 subjects randomized. Baseline data for CDR‐SB and MMSE are consistent with recently enrolled MCI due to AD (prodromal AD) studies. Subject demographics, screen failure information, safety and dropout information will be presented at the meeting. Conclusions: HOPE4MCI represents the first and only Phase 3 clinical trial targeting the reduction of hippocampal overactivity for slowing the progression of MCI due to AD. The HOPE4MCI trial is supported, in part, by R01AG061091 to RM and R01AG048349 to MG.